1991
DOI: 10.1029/91wr00478
|View full text |Cite
|
Sign up to set email alerts
|

Statistical estimation and interpretation of trends in water quality time series

Abstract: Three approaches to trend analysis of water quality time series are discussed: (1) seasonal model, with a test for trend based on ranks of observations, with observations assumed to be m dependent; (2) transfer function noise model, in which covariate series may be included by means of transfer functions, with the remaining noise modeled as a seasonal autoregressive moving average process; and (3) component model, with the noise decomposed into series which describe trends, and irregular and seasonal variation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

1992
1992
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(31 citation statements)
references
References 23 publications
1
30
0
Order By: Relevance
“…ven Belle & Hughes, 1984;Cailas et al, 1986;Hipel et al, 1988;Hipel & McLeod, 1994;Taylor & Loftis, 1989;Demarée & Nicolis, 1990;Zetterqvist, 1991;Chiew & McMahon, 1993;Yu et al, 1993;Hirsch et al, 1993;Lettenmaier et al, 1994;Burn, 1994;Yulianti & Burn, 1998;Gan, 1998;Lins & Slack, 1999;Douglas et al, 2000;Yue et al, 2003; and others). Another rank-based nonparametric test, the Spearman's rho (SR) test (Lehmann, 1975;Sneyers, 1990), has sometimes been applied to detect trends in hydrological data (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…ven Belle & Hughes, 1984;Cailas et al, 1986;Hipel et al, 1988;Hipel & McLeod, 1994;Taylor & Loftis, 1989;Demarée & Nicolis, 1990;Zetterqvist, 1991;Chiew & McMahon, 1993;Yu et al, 1993;Hirsch et al, 1993;Lettenmaier et al, 1994;Burn, 1994;Yulianti & Burn, 1998;Gan, 1998;Lins & Slack, 1999;Douglas et al, 2000;Yue et al, 2003; and others). Another rank-based nonparametric test, the Spearman's rho (SR) test (Lehmann, 1975;Sneyers, 1990), has sometimes been applied to detect trends in hydrological data (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Such detrending treatment can certainly affect the estimated value of β and hence the validity of (or confidence in) any inference made regarding the statistical significance of temporal trends in the time series. This somewhat circular issue is beyond the scope of our current work -it has been previously discussed in the context of short-term memory (Zetterqvist, 1991;Darken et al, 2002;Yue et al, 2002;Noguchi et al, 2011;Clarke, 2013;Sang et al, 2014), but it is not well understood in the context of fractal scaling (or long-term memory) and hence presents an important area for future research.…”
Section: Motivation and Objective Of This Workmentioning
confidence: 84%
“…B4 and B5 were implemented using the na.locf function in the zoo R package (Zeileis and Grothendieck, 2005). B7-B11 were implemented using the loess function in the stats R package (R Development Core Team, 2014).…”
Section: Summary Of Estimation Methodsmentioning
confidence: 99%
“…A benefit of this test is that no assumptions about the probability distribution of the data are needed. It has been widely used in the hydro-climatological literature; therefore, details of its calculation are not presented in this study, but can be found in Hipel et al (1988), Zetterqvist (1991), Chiew and McMahon (1993), Burn (1994), Yulianti and Burn (1998), Lins and Slack (1999), Douglas et al (2000), Yue and Wang (2004), Yue and Pilon (2004), Burn et al (2008), Drapela (2011) and Mondal et al (2012). In the same sense, to estimate the true slope of an existing trend as change per year, the Sen nonparametric method was calculated (Theil 1950, Sen 1968.…”
Section: General Analysis Of the Historic Streamflowsmentioning
confidence: 99%